Călugăra din Caraş-Severin - Trifa, Alin (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
The Călugăra Monastery, of very small dimensions, is located (near the town of Oraviţa) at the end of a very steep road, where only those who come specifically for their spiritual benefit end up. The isola- tion, the miraculous icon of the Mother of God, the community of monks and especially the life in this place of two monks, sometime in the eighteenth century, made many compare the monastery and the experiences here, with the places and the spiritual atmosphere from the Holy Mount Athos. In 1859, a cave was discovered in which there was a stone altar, an icon of the Mother of God with the Baby, some church objects, but also some holy relics, those of the hermit Eftimie who lived here. The construction of the monastery church was completed in 1862. In 2015, the works of mural painting of the church began in the tech- nique of secco.